To simplify the expression \( 12(9 - 70) + (-29)0 \), we start by simplifying the components step by step.
-
Calculate the multiplication with 0: \( (-29)0 = 0 \). So, the expression simplifies to: \[ 12(9 - 70) + 0 = 12(9 - 70) \]
-
Calculate the subtraction inside the parentheses: \( 9 - 70 = -61 \). Now the expression is: \[ 12(-61) \]
-
Calculate the multiplication: \( 12 \times (-61) = -732 \).
Now we have simplified the expression to \( -732 \).
Next, we need to check which of the provided responses is equivalent to \( -732 \):
-
Evaluate \( 12(9 - 1) + 1 \): \[ = 12(8) + 1 = 96 + 1 = 97 \]
-
Evaluate \( \frac{1}{2}(9 - 1) + 1 \): \[ = \frac{1}{2}(8) + 1 = 4 + 1 = 5 \]
-
Evaluate \( 12(2) + 1 \): \[ = 12(2) + 1 = 24 + 1 = 25 \]
-
Evaluate \( \frac{1}{2}(2) + 1 \): \[ = \frac{1}{2}(2) + 1 = 1 + 1 = 2 \]
-
Evaluate \( 12(9 - 0) + 0 \): \[ = 12(9) + 0 = 108 + 0 = 108 \]
-
Evaluate \( \frac{1}{2}(9 - 0) + 0 \): \[ = \frac{1}{2}(9) + 0 = 4.5 + 0 = 4.5 \]
-
Evaluate \( 12(9 - 1) - 1 \): \[ = 12(8) - 1 = 96 - 1 = 95 \]
None of the options provided yield \( -732 \). After re-evaluating the original expression \( 12(9 - 70) + (-29)0 = 12(-61) = -732 \), it appears there may be an issue. If you intended to find a numerical equivalent expression among the options listed, none of them equal \( -732 \).
Please check again, or clarify if there was a specific method or condition that should be applied to the expressions that could yield \( -732 \).